Pyrrolidine and Indolizidine Alkaloids from Chiral N-tert-Butanesulfinyl Imines Derived from 4-Halobutanal - Sirvent, Ana; Hernández-Ibáñez, Sandra; Yus, Miguel; Foubelo, Francisco (Synthesis, 2021)
An efficient stereocontrolled preparation of 2-substituted pyrrolidines and 5-substituted indolizidin-7-ones, by using chiral N-tert-butanesulfinyl imines derived from 4-halobutanal as starting materials, is detailed. Addition of Grignard reagents and a decarboxylative Mannich reaction with β-keto acids involving these chiral imines proceeded with high diastereoselectivity. The synthesis of the pyrrolidinic alkaloids (–)-bgugaine, (+)-villatamine B, (–)-norhygrine, trans-dendrochrysanine, and (–)-ruspolinone demonstrated the utility of this methodology.
Keywords: chiral sulfinyl imines; diastereoselective additions; decarboxylative Mannich reaction; bgugaine; villatamine; norhygrine; trans-dendrochrysanine; ruspolinone